Hydroclimatic and geothermal controls of lithium brine deposits on the Qinghai-Tibetan Plateau. Issue 4 (March 2020) - Gao, Chunliang; Yu, Junqing; Min, Xiuyun; Cheng, Aiying
Abstract: The paper focused on the distribution characteristic, material source and ore-forming mechanism of lithium brine deposits on the Qinghai-Tibetan Plateau, and established the lithium brine deposit model. The results showed that all lithium brine deposits are controlled by the Neotectonics, enclosed/semi-enclosed low catchment basin and hyper-arid climate conditions, and related to the Cenozoic hydrothermal activities. The ore-forming materials especially lithium element are derived from volcanic rocks, which migrated and concentrated after water-rock interaction by hydrothermal springs and atmospheric precipitation.